Work Stress In Finatama Bandung Affects Individual Performance - Laelawati, Kania; Komariyah, Imas (SEIKO : Journal of Management & Business, 2023)
This study aims to identify the predominant kind of stress affecting employee performance at BPR Finatama and examine the factors that influence work stress in individuals and organisations and have an impact on individual performance. 57 employees who were selected at random from the general public were used as a sample in this explanatory study. The information was gathered using a Likert scale questionnaire. The data were examined by multiple linear regression using the SPSS 23.0 programme. The hypothesis test made use of the validity and reliability tests, the traditional assumption test, and the F and t tests. The results of this study indicate that both individual and collective stressors have an effect on employee performance. The results of this study show that employee performance decreases as employee stress increases, and that employee performance increases as employee stress decreases. Leaders at BPR Finatama should be able to participate more actively in each activity or group task and offer rewards to staff members to ensure that every work is completed correctly in order to improve employee performance. Keywords: Stress Work, Performance, Performance Employee